Implementation of Event-Driven Architecture using NATS JetStream for a Large-Scale Online Exam Answer Collection System - Dery Ciputra Ma’soem; Novi Rukhviyanti (Journal of Business, Social and Technology, 2026)
Background: Online examination systems—even at the prototype and institutional levels—face serious performance challenges under synchronized spike conditions. This study, conducted on a prototype (Chilaedu) with 300 synthetic users, demonstrates that conventional synchronous (request-response) architecture has thread-capacity limitations that trigger gateway timeout failures, thereby undermining overall assessment system reliability. Objective: This research designs and evaluates the architectural transition toward an asynchronous Event-Driven Architecture (EDA) approach using the Go runtime and the NATS JetStream message broker on the Chilaedu e-learning platform prototype. Methods: System performance was evaluated using a load-testing scenario based on a custom testing tool developed with Go and Python to simulate synchronized spike conditions at concurrency levels of 10, 25, 50, and 100, with 300 synthetic user entities per scenario, in a single-server isolated prototype environment. Results: The test results show that the asynchronous architecture successfully maintained a throughput of 2,209 requests per second with an HTTP error rate of 0.00%. The system operated efficiently with an average memory consumption of 70 MB and a peak CPU utilization of 18.03%. Latency at the 99th percentile (p99) was recorded at 79.02 ms, which is below the feasibility threshold of 100 ms, thereby preventing user interface freezes (browser freezes). A comparison with the synchronous monolithic approach documented in previous research shows a significant increase in load-handling capacity. Conclusion: The NATS JetStream-based EDA architecture proves effective as a solution for improving the reliability and efficiency of large-scale online exam answer collection infrastructure.